Cross-validation of prediction equations for estimating the body mass index in adults without the use of body weight - Júlio César Chaves Nunes Filho; Marilia Porto Oliveira Nunes; Robson Salviano de Matos; Daniel Vieira Pinto; Dyego Castelo Branco Holanda Gadelha Pereira; Thais Amanda Silva Pereira Castelo Branco; Geraldo Bezerra da Silva Júnior; Janaina de Almeida Mota Ramalho; Elizabeth de Francesco Daher (PLoS ONE, 2025)
Introduction Body Mass Index (BMI) is a widely accepted measure by the World Health Organization for assessing body composition, as it provides critical insights into health risks, life expectancy, and quality of life. However, in resource-limited settings, access to weighing scales is often inadequate, and environmental conditions, such as unstable terrain, may hinder accurate weight measurements. In these contexts, alternative methods for estimating BMI become essential for effective health assessment. This study aimed to develop and validate equations to estimate BMI without relying on body weight, providing a practical tool for nutritional assessment where traditional methods are not feasible. Materials and methods Adults aged 18 to 59 of both sexes were included. Variables like waist circumference, height, hip circumference, age, and weight were used for equation development and validation. Participants were divided by sex, with regression and validation subgroups for each. Statistical tests included Student’s t-tests, Pearson correlation, Stepwise Regression, Intraclass Correlation Coefficient, Weighted Kappa Coefficient, and Bland-Altman statistics. Results The study included 810 adults, with 63% (576) women. No significant differences were found in paired comparisons between regression and validation subgroups for both sexes (p > 0.05). Four equations were proposed for BMI estimation: EM2 and EM3 for males, and EF2 and EF3 for females. All equations showed strong positive correlations (r > 0.90), significant at p < 0.05. Regression analysis revealed R2 values between 0.861 and 0.901 (p < 0.000). Intraclass Correlation Coefficient values indicated agreement of 0.961 and 0.972 (p < 0.05), with Weighted Kappa values showing substantial agreement of 0.658 and 0.711 for both sexes (p < 0.05). Conclusion Adopting the proposed equations for estimating BMI in adults without using body weight is safe and effective for measuring this body measure in this population, particularly when weighing these individuals is not feasible.